The MFA: Its costs and consequences - Dean Spinanger; Joachim Zietz (Intereconomics, 1986)
The present Multi-Fibre Arrangement expires on July 31st. What are the arguments voiced by the proponents of a further extention? What would be the effects of a reduction in protectionism on the textile and clothing industries?
Keywords: 330; Multi-Fibre Arrangement